Media and the Case of State Capture in South Africa: How Independent Outlets Aided Whistleblowers in Communicating their Messages - Ugljesa Radulovic (Clinical Sociology Review)
State capture, which is when private actors influence the state through illegal and non-transparent forms, significantly impacted South Africa’s socio-political landscape during Jacob Zuma’s presidency. This transpired largely because of an unethical nexus that formed around Zuma, those in government loyal to him, and the powerful business family – the Guptas. These revelations came to the fore because of independent media, which focused on exposing the illicit relationships driving state capture. Independent media was reliant on whistleblowers to communicate a complete narrative, which resulted in a mutually beneficial collaboration between independent media and whistleblowers. A qualitative research approach employing two methods was utilised to examine this collaboration. The dominant source of information arose from semi-structured interviews conducted with whistleblowers and independent media outlet affiliates. This data was further supplemented with document analysis. This study found that independent media played a crucial role in providing support to state capture whistleblowers. Support occurred in three forms, namely: defensive; emotional; and offensive support. Defensive support entailed legal, financial and security aid. Emotional support was provided in the form of informal counselling. Offensive support entailed using media exposure to make the whistleblowers’ narratives public, as well as mediating between whistleblowers and official commissions of inquiry.